Simultaneous Estimation of Chlordiazepoxide and Clidinium Bromide in Combined Dose Tablet by High Performance Thin Layer Chromatography - G. Walode, Sanjay; B. Bagade, Shashikant; P. Rode, Madhuri; R. Tajne, Madhukar (Asian Journal of Chemistry, 2016)
A simple, accurate, precise and economical high performance thin layer chromatographic method for simultaneous estimation of chlordiazepoxide and clidinium bromide in tablet form has been developed. It was performed on silica gel 60 GF254 thin layer chromatographic plates using mobile phase comprising of methanol : acetonitrile : water : glacial acetic acid in the ratio 2.0 : 6.5 : 1.0 : 0.5 and the detection was carried out at 217 nm. The Rf values were 0.83 for chlordiazepoxide and 0.30 for clidinium bromide. The linear response was observed over 2.2–12.2 g of chlordiazepoxide and 1.2–8.8 g of clidinium bromide both by height and by area. The recovery of the drugs from tablet carried out by standard addition method was found to be 99.31 ± 1.25 (by height) and 98.06 ± 1.45 (by area) for chlordiazepoxide and 102.66 ± 1.53 (by height) and 100.04 ± 1.79 (by area) for clidinium bromide. The method was validated with respect to its accuracy, precision, specificity and ruggedness.